(untitled) (JOURNAL OF ANALYTICAL SYNERGY AND SCIENTIFIC HORIZON, 2025)
Intercultural communication: the topic of difficulties and opportunities in learning a foreign language is very interesting and relevant. This topic allows you to study not only the aspects of learning a foreign language in the process of language teaching, but also related to intercultural differences, difficulties and new opportunities. The thesis, on the other hand, presents some problems and thus suggestions.